Designing Content for A Web-Based Application Used in Blended Composition Classes: Things to Consider in The EFL/ESL Context - Rifai, Irfan (Humaniora, 2014)
In the world of composition teaching, teachers of writing play just as vital role. Their tasks are demonstrating, motivating, supporting, responding, and evaluating. The days of these teachers are often filled with editing and additional feedback sessions. Thus, in order to have a web especially designed as a tool for learning to write in ESL, the five tasks mentioned by Harmer should be made as important points to consider (teachers? preferences). The content of such web should be also based on careful considerations that include factors like students? preferences (user experience). It is to make sure that the web being created meets the preference of the users. With the thoughts, two groups of students were gathered in a study involving two writing classes in which online technology being used as a platform for students and Instructor to exchange ideas, review and edit drafts, provide writing tips links and leave comments on others? pieces of writing. Students? online activities were observed and their feedback during group discussion was used as the base to construct the content of the web.